Publisher Correction: Global hotspots for the occurrence of compound events - Nina N. Ridder; Andy J. Pitman; Seth Westra; Anna Ukkola; Hong X. Do; Margot Bador; Annette L. Hirsch; Jason P. Evans; Alejandro Di Luca; Jakob Zscheischler (Nature Communications, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-20502-8.